P436 Efficacy and safety of biosimilars of anti-TNF-a in paediatric-onset Inflammatory Bowel Disease: Data from the Sicilian Network for Inflammatory Bowel Diseases (SN-IBD). (21st January 2022) - Dipasquale, V; Pellegrino, S; Cucinotta, U; Citrano, M; Graziano, F; Cappello, M; Busacca, A; Orlando, A; Accomando, S; Romano, C
Abstract: Background: Few data regarding the use of biosimilars of anti-tumour necrosis factor-a (TNF-a) in children with Inflammatory Bowel Disease (IBD) have been reported. We aimed to assess the efficacy and the safety of biosimilars of infliximab (IFX) and adalimumab (ADA) in paediatric-onset IBD. Methods: This was a multicentre, observational, retrospective study performed among the cohort of the Sicilian Network for the Inflammatory Bowel Disease (SN-IBD) and including all patients with paediatric-onset IBD treated with the biosimilars of IFX or ADA. Demographic and clinical data were collected from medical records. PUCAI and PCDAI scores at the time of IFX start, after, 14 and, 54 weeks were recorded. The primary outcome was the rate of clinical remission at weeks, 14 and, 54. Secondary outcomes included treatment duration and incidence of adverse events. Results: They were included, 128 patients, of whom, 87 on IFX biosimilar (group, 1) and, 41 on ADA biosimilar (group, 2) (Table 1). Table, 1.Baseline characteristics of patients At week, 14, UC patients on IFX biosimilar had a median PUCAI score of, 10 (IQR, 5.0–22.5), while CD patients a median PCDAI score of, 5 (IQR, 5.00–10.8). Overall, the remission rate on IFX biosimilar at week, 14 was, 61.5%, and it was significantly associated with positive family history [OR, 13.18 (2.44–245.65, p=0.015)], older age at starting biosimilar [OR, 1.19 (1.02–1.41, p=0.038)], and diagnosis of CD (in comparison to UC) [OR, 3.45 (1.35–9.23, p=0.011)]. At week, 54, both UC and CD patients on IFX biosimilar had a median clinical score of, 5. The remission rate was, 69.1%, and no significant association with any variable was found. Patients on ADA showed a remission rate of, 75% at, 14 weeks, and of, 70% at, 54 weeks, both associated with shorter disease duration [OR, 0.67 (0.45–0.93, p=0.025) and OR, 0.55 (0.28–0.86, p=0.026), respectively]. At, 54 weeks, patients on IFX showed a >90% failure-free survival (Figure, 1), which was inversely associated with the presence of extraintestinal manifestations (HR, 5.12, p=0.014) and non-naive patients (HR, 3.81, p=0.025). Patients on ADA biosimilar had >83% failure-free survival at, 12 months (Figure, 2), associated with shorter disease duration (HR, 1.41, p=0.043). About safety, a total of, 13 adverse events were registered, 9 in group, 1 (incidence of, 6.13/100 PY) and, 4 in group, 2 (incidence of, 12.23/100 PY). Most (n=7) were acute infusion reactions. Figure, 1.Failure-free survival on IFX biosimilar Figure, 2.Failure-free survival on ADA biosimilars Conclusion: This is one of the largest cohorts of paediatric-onset IBD on biosimilars, and confirmed these drugs are effective and safe in this group of patients, with high percentage of failure-free survival at, 1 year and low incidence of mild adverse events.